Kebijakan Pariwisata Syariah Untuk Peningkatan Pembangunan Ekonomi Daerah Surabaya - Karen Katalina; Kyky Wulandari; Tri Wahyuningsih; Desi Fatmawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Sharia tourism policy is a government effort to develop the tourism sector by prioritizing sharia principles in all aspects. These measures include services that value Islamic teachings, such as sharia-based places to stay, restaurants that serve halal food, and entertainment programs that adhere to Islamic ethics. The aim of this policy is to increase the attractiveness of tourism among Muslim tourists and at the same time create a tourist environment that is in accordance with Islamic teachings. Thus, the sharia tourism policy is expected to contribute positively to economic growth and fulfillment of the spiritual needs of the local community. sharia tourism is the implementation of sharia principles into a form of travel activities of sharia tourist destinations. The development of Islamic tourism is currently growing rapidly because it is very much in demand by Muslim tourists who are looking for alternative travel in accordance with the principles of Islamic sharia, this research reaches the implementation of the concept of Islamic tourism in tourist destinations that are very popular and in great demand in areas with a majority Muslim population. This research uses a qualitative approach that analyzes accommodation, culinary, and tourist activities that integrate Islamic values, the results of this study show that Islamic tourism policies have a significant impact on the economic development of the region, this research discusses the Islamic tourism system and its policies where these two things have a significant impact on local economic development, through a case study approach and economic data analysis, this research identifies the effect of regional tourism policies on regional economic development.